Pituitary Metastasis of Clear Cell Renal Carcinoma Mimicking Pituitary Macroadenoma – Case Report - Lucas Caixeta Nogueira; Luciano Ricardo França da Silva; Luiz Eduardo Mendonça Tenório; Cleiton Onofre de Menezes; João Victor Franco de Oliveira Calado; Luiz Felipe Gomes Rosa; Guilherme Figner Moussalem; Nicolai Máximo Leventi (Brazilian Neurosurgery, 2024)
Introduction Pituitary tumors account for 25% of all primary brain tumors and for 15% of overall intracranial expansive masses. Pituitary metastases, in contrast, are a rare condition, estimated as 1.8% of all resected sellar lesions. We present here a rare case of clear cell renal carcinoma metastasis to the pituitary gland.